PENGARUH KONEKSI POLITIK, INTENSITAS ASET TETAP, KOMISARIS INDEPENDEN, PROFITABILITAS DAN LEVERAGE TERHADAP TAX AVOIDANCE - Sahrir Sahrir; Sofyan Syamsuddin; Sultan Sultan (Jurnal Penelitian Ekonomi Akuntansi, 2021)
Tax avoidance is a business that is conducted legally by the company by utilizing existing loopholes in the tax regulations with the aim of minimizing or even avoiding tax payments. This research aimed to know and analyze the effect of political connections, fixed assets intensity, independent commissioners, profitability and leverage to tax avoidance. The method used is quantitative, where the data used is secondary data formed as financial statements of banking sector companies listed on the Indonesia Stock Exchange for the period 2014-2018. The sample determination used purposive sampling, so obtained financial statements that meet the research criteria of 172 observations. The data analysis technique used multiple linier regression analysis. The research result showed that political connections, fixed assets intensity, profitability and leverage affected to the tax avoidance. While independent commissioners is not affected to the tax avoidance